Alloy powder, its manufacturing method, and uses
The solidification of alloy melts into endogenous alloy powders with a coating phase addresses the challenges of purity and impurity control in metal powder production, enabling high-purity, single-crystal alloy powders suitable for diverse applications.
Patent Information
- Application Number
- JP2023519406
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-30
- Filing Date
- 2021-09-26
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2041-09-26
AI Technical Summary
Existing methods for producing metal and alloy powders face challenges such as low yield, high cost, complex processes, difficulty in achieving high purity, and controlling impurity content, particularly oxygen, which affects their performance.
A method involving the solidification of an alloy melt to produce a metallic material composed of an endogenous alloy powder and a coating, where the alloy powder precipitates during initial solidification, ensuring a dispersed particle phase is coated by a matrix phase, with specific elemental compositions to prevent intermetallic compound formation and control impurity distribution.
This method enables the production of high-purity alloy powders with controlled impurity levels, particularly oxygen, achieving a high percentage of single crystal particles and allowing for efficient removal of the coating to maintain purity and activity, suitable for various applications including 3D printing and composite materials.
Smart Images

Figure 0007617671000001 
Figure 0007617671000002 
Figure 0007617671000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of metallic materials technology, and in particular to an alloy powder, a manufacturing method thereof, and applications thereof. [Background technology]
[0002] Micro-nanoparticle sized metal powders exhibit many properties different from conventional materials in optics, electricity, magnetism, catalysis, etc. due to special surface effects, quantum size effects, quantum tunneling effects, Coulomb blocking effects, etc., and are widely used in many fields such as optoelectronic devices, sound-absorbing materials, and highly efficient catalysts.
[0003] Traditionally, the methods for producing metal powders are divided into solid-phase, liquid-phase and gas-phase methods according to the state of the material. The solid-phase methods mainly include mechanical grinding, ultrasonic grinding, pyrolysis and explosion, while the liquid-phase methods mainly include precipitation, alkoxide, carbonyl, spray-heat drying, freeze-drying, electrolysis and chemical condensation, while the gas-phase methods mainly include gas-phase reaction, plasma, high-temperature plasma, deposition and chemical vapor deposition. There are many methods for producing metal powders, but each method has certain limitations. For example, the disadvantages of the liquid-phase method are low production volume, high cost and complicated process. The disadvantages of the mechanical method are that it is difficult to classify the powder after production, and it is difficult to guarantee the purity, fineness and morphology of the product. The rotating electrode method and the gas atomization method are currently the main methods for producing high-performance metal and alloy powders, but they have low production efficiency, low yield of ultrafine powder and relatively large energy consumption. The jet mill method and hydrogenation / dehydrogenation method are suitable for large-scale industrial production, but they are highly selective for the raw metals and alloys. Furthermore, the impurity content of metal or alloy powder, especially the oxygen content, has a significant impact on its performance. Conventionally, the impurity content in metal or alloy powder has been controlled mainly by controlling the purity of the raw materials and the degree of vacuum, but this is costly. Therefore, it is of great significance to develop a new manufacturing method for high-purity metal powder materials. Summary of the Invention [Problem to be solved by the invention]
[0004] Based on this, in order to meet the above technical challenges, there is a need to provide a method for producing high purity alloy powder materials, which has a simple process, low cost and easy operation. [Means for solving the problem]
[0005] In order to solve the above technical problems, the present invention proposes the following technical content.
[0006] The metallic material composed of the intrinsic alloy powder and the cladding is produced by solidifying the alloy melt, and includes an intrinsic dispersed particle phase precipitated during the initial alloy solidification process and a matrix phase covering the dispersed particles, which correspond to the intrinsic alloy powder and the cladding, respectively. The elemental composition of the intrinsic alloy powder is mainly M. a1 A b1 T c1 The elemental composition of the coating is mainly A b2 T c2 M and A each include one or more metal elements, T is an impurity element including oxygen, a1, b1, c1, b2, c2 respectively represent the atomic percent content of the corresponding composition elements, and a1+b1+c1=100%, b2+c2=100%, c2>c1>0, b1>0, and the melting point of the intrinsic alloy powder is the above Higher than the covering, The above intrinsic alloy powder The A element is dissolved in solid solution, and no intermetallic compound is formed between the above M and A. 1 -A 1 and wherein M is one or more of the combinations of elements. 1 represents any element of M, and A 1 represents any element of A, and the above Even if the metallic material consisting of the intrinsic alloy powder and the cladding is completely melted and then resolidified, no intermetallic compound consisting of the main element of M and the main element of A is formed, The above intrinsic alloy powder and The above-mentioned covering The main element of M is M 1 -A 1M that satisfies the element combination conditions 1 It is composed of elements, and the main element of A is M 1 -A 1 A satisfies the element combination conditions 1 It is characterized by being composed of elements.
[0007] Supplementary explanation: "T is an impurity element containing oxygen" means that T is an impurity element and also contains the O element.
[0008] The solidification method of the initial alloy melt includes normal casting, continuous casting, molten strip casting, melt drawing, etc. The particle size of the intrinsic alloy powder is related to the solidification rate of the initial alloy melt. Generally speaking, the particle size of the intrinsic alloy powder is negatively correlated with the solidification rate of the initial alloy melt, that is, the higher the solidification rate of the initial alloy melt, the smaller the particle size of the intrinsic alloy powder.
[0009] Furthermore, the solidification method of the above-mentioned initial alloy melt does not include a solidification method corresponding to the atomization pulverization technology.
[0010] Supplementary explanation: The solidification rate range of the above initial alloy melt is 0.001K / s to 10 8 K / s.
[0011] Furthermore, the solidification rate range of the initial alloy melt is 0.001K / s to 10 7 K / s.
[0012] Furthermore, the particle size range of the intrinsic alloy powder is 3 nm to 10 mm.
[0013] Supplementary explanation: the particle size range of the above intrinsic alloy powder is 3 nm to 1 mm.
[0014] Preferably, the particle size of the intrinsic alloy powder is in the range of 3 nm to 500 μm.
[0015] Preferably, the particle size of the intrinsic alloy powder is in the range of 3 nm to 99 μm.
[0016] Preferably, the particle size of the intrinsic alloy powder is in the range of 3 nm to 25 μm.
[0017] Preferably, the particle size of the intrinsic alloy powder is in the range of 3 nm to 10 μm.
[0018] Furthermore, the particle shape of the intrinsic alloy powder is not limited and may include at least one of branched, spherical, nearly spherical, square, discoid, and rod-shaped, and when the particle shape is rod-shaped, the particle size specifically refers to the diameter dimension of the cross section of the rod.
[0019] The shape of the metallic material composed of the intrinsic alloy powder and the coating is related to the solidification method. When the solidification method is continuous casting, the shape is generally slat-like, when the solidification method is melt stripping, the shape is generally strip-like or thin plate-like, when the solidification method is melt drawing, the shape is generally mainly thread-like. The faster the solidification rate, the thinner, finer and narrower the cross section of the metallic material composed of the obtained intrinsic alloy powder and the coating will be, and conversely, the slower the solidification rate, the thicker, coarser and wider the cross section will be.
[0020] Furthermore, the shape of the metallic material composed of the intrinsic alloy powder and the coating does not include the powder shape of the product corresponding to the atomized powder manufacturing technology.
[0021] Furthermore, the initial alloy melt is solidified by a melt stripping method, and the solidification rate is 100K / s to 10 7 At K / s, a strip of metallic material consisting of endogenous alloy powder and cladding with a thickness of about 10 μm to 5 mm is obtained, with the particle size range of the endogenous alloy powder being 3 nm to 200 μm.
[0022] Furthermore, when the initial alloy melt is solidified by a method such as normal casting or continuous casting, and the solidification rate is 0.001 K / s to 100 K / s, a bulk metal material is obtained that is composed of an intrinsic alloy powder and a coating, and in which the particle size range of the intrinsic alloy powder is 200 μm to 10 mm and at least one dimension in the three-dimensional scale direction exceeds 5 mm.
[0023] Supplementary explanation: Furthermore, the metal material composed of the above-mentioned endogenous alloy powder and the coating body is in a band shape, and the thickness of the band is 5 μm to 5 mm.
[0024] Furthermore, the metal material composed of the intrinsic alloy powder and the coating is in the form of a strip, and the thickness of the strip is 10 μm to 1 mm.
[0025] Furthermore, the lower limit of the volume percentage content of the endogenous alloy powder in the metal material composed of the endogenous alloy powder and the coating body is 1%, and the upper limit is a volume percentage content corresponding to the requirement that the endogenous alloy powder can be dispersed in the coating body.
[0026] Since the volume correlation is directly related to the dispersibility of the intrinsic alloy powder, when considering how much of the intrinsic alloy powder can be dispersed and distributed in the coating, it is necessary to accurately evaluate the volume percentage content of the intrinsic alloy powder. The above volume percentage content can be converted from the relationship between the density, atomic weight, and atomic percentage content of each element. When the matrix element of the coating is a large atomic element, the matrix can obtain a higher volume percentage content by a smaller atomic percentage content, thereby greatly increasing the content of the intrinsic alloy powder that can be coated. For example, when the atomic percentage composition is Ce, 50 Ti 50 In the alloy melt, the weight percentage contents of Ce and Ti are 74.53wt% and 25.47wt%, respectively, and the density of both is 6.7g / cm3. 3 and 4.5g / cm 3 , so that the atomic percentage composition is Ce 50 Ti 50It can be calculated that the volume percentage contents of Ce and Ti in the alloy melt are 66 vol% and 34 vol%, respectively. When Ti precipitates from the melt, its volume percentage content is only about 34 vol%, even without considering solid solutions and impurities. It shows that even if the atomic percentage content of Ti in the Ce-Ti alloy exceeds 50%, its volume percentage content can still be significantly lower than 50%, which is favorable for obtaining dispersed Ti particles.
[0027] The application of metal materials composed of endogenous alloy powder and cladding mainly depends on the application effect of the endogenous alloy powder, so the cladding needs to be removed later. Therefore, if the volume percentage content of the endogenous alloy powder is less than 1%, the cladding material will be wasted greatly, and the practical significance of the material application will be lost.
[0028] Different alloy systems and different solidification rates produce different sizes and shapes of endogenous alloy powders. For example, when the cooling rate is fast and the endogenous alloy powders are mainly small spherical or nearly spherical nanopowder, the grain growth is limited, and it is easy to maintain a certain space and distance between the grains, and a higher volume percentage content can be achieved under the dispersed distribution of the endogenous alloy powder. When the cooling rate is slow and the endogenous alloy powders are mainly coarse dendritic, the grain growth is sufficient, and the various grains are easy to contact, fuse and intertwine during the growth process, and a lower volume percentage content can be achieved under the dispersed distribution of the endogenous dendritic alloy particles.
[0029] Preferably, the volume percentage content of the intrinsic alloy powder in the metal material composed of the intrinsic alloy powder and the coating is in the range of 5% to 50%.
[0030] More preferably, the volume percentage content range of the intrinsic alloy powder in the metal material composed of the intrinsic alloy powder and the coating is 5% to 40%, with the preferred lower limit ensuring economic efficiency and the preferred upper limit fully ensuring that the intrinsic alloy powder can be dispersed and distributed in the coating.
[0031] The intrinsic alloy powder solidifies and precipitates from the initial alloy melt, and according to nucleation and growth theory, whether it is an approximately spherical nanoparticle that has just undergone nucleation and growth, or a fully grown micron- or millimeter-order dendritic particle, the growth of the crystal has a certain orientation relationship, so that each precipitated single particle is mainly composed of one single crystal.
[0032] When the volume percentage content of the endogenous alloy powder is high, it is not excluded that two or more particles will be bonded together during the endogenous precipitation process of the single crystal particles. If two or more single crystal particles are weakly agglomerated, adsorbed to each other, or only bonded at a few sites in contact with each other, and are not fully bonded to form one particle by normal grain boundaries like polycrystalline materials, they are still two single crystal particles. The characteristic is that after the matrix phase is removed in the later process, these single crystal particles can be easily separated by techniques including ultrasonic dispersion treatment, jet mill grinding, etc. However, it is difficult to separate the grain boundaries of normal ductile metal or alloy polycrystalline materials by techniques including ultrasonic dispersion treatment, jet mill grinding, etc.
[0033] Preferably, the number of single crystal grains in said intrinsic alloy powder accounts for 60% or more of the total number of grains.
[0034] More preferably, the number of single crystal grains in the intrinsic alloy powder accounts for 75% or more of the total number of grains.
[0035] More preferably, the number of single crystal grains in the intrinsic alloy powder accounts for 90% or more of the total number of grains.
[0036] Supplementary explanation: In the metallic material composed of the above-mentioned intrinsic alloy powder and coating, both the intrinsic alloy powder and the coating are in a crystalline state.
[0037] The elemental composition of the above intrinsic alloy powder is mainly M a1 A b1 T c1 The elemental composition of the coating is mainly A b2 T c2where M and A each contain one or more metal elements, T is an impurity element including oxygen, a1, b1, c1, b2, and c2 each represent the atomic percent content of the corresponding composition element, and a1+b1+c1=100%, b2+c2=100%.
[0038] Characterizing the composition of each element by its atomic percent content allows the increase / decrease and change in element content, such as the increase / decrease and change in impurity elements, to be correctly expressed in terms of the quantity of substance concept. Characterizing the content of each element by its mass percentage content (or ppm concept) can easily lead to erroneous conclusions, since the atomic weights of each element are different. For example, if the atomic percent content of Ti 45 Gd 45 O 10 The alloy contains 100 atoms with an atomic percent content of O of 10 at%. 45 O4 (atomic percent composition is Ti 91.8 O 8.2 ) and Gd 45 O6 (atomic percent composition is Gd 88.2 O 11.8 If we divide it into two parts, Gd 45 The atomic percent content of oxygen in O6 increases to 11.8 at% and Ti 45 The atomic percent content of oxygen in O4 is reduced to 8.2 at%, which can be used to correctly represent the enrichment of O in Gd. However, if the mass percent content of O is used, the Ti 45 Gd 45 O 10 The mass percentage content of O is 1.70 wt%, and Ti 45 O4 and Gd 45 The mass percentage contents of O in O6 are 2.9 wt.% and 1.34 wt.%, respectively, and Ti 45 The O content of O4 is Gd 45 This leads to the erroneous conclusion that the O content in O6 is significantly increased compared to that in O.
[0039] moreover, The above intrinsic alloy powder The melting point of coveringIf this condition is met, when the initial alloy solidifies, the matrix phase solidifies last, covering the intrinsic alloy powder.
[0040] moreover, The above intrinsic alloy powder A element is dissolved in solid solution, that is, 0 <b1である。
[0041] Preferably, 0 <b1≦15%であり、すなわちM a1 A b1 T c1 The A element (atomic percent content) can be dissolved in 15% or less of M. a1 A b1 T c1 The solubility of A in intrinsic alloy powders also depends on the major element composition, impurity content, and solidification rate of a particular alloy melt. In general, more A elements can be dissolved when the melt solidifies faster and smaller intrinsic alloy powders, such as nanopowder, are formed.
[0042] Furthermore, the intrinsic alloy powder contains a certain amount of impurity T, and the content of the T impurity element in the intrinsic alloy powder is lower than the content of the corresponding T impurity element in the cladding, i.e., c2>c1>0. This means that in the metal material composed of the intrinsic alloy powder and the cladding produced by alloy melting and solidification, the impurity element is covering At the same time, endogenous alloy powder is purified.
[0043] Furthermore, the above T is an impurity element such as O, H, N, P, S, F, Cl, etc., including oxygen, and is 0 <c1≦1.5%である。
[0044] Supplementary explanation: That is, T contains O, and the O content is greater than 0. If a specific element among the above H, N, P, S, F, and Cl elements is not contained, its content is 0, and if it is contained, its content is greater than 0 and the content of T is the total content of O, H, N, P, S, F, and Cl elements.
[0045] Preferably, the above T is an impurity element such as O, H, N, P, S, F, or Cl, including oxygen, and 0.01%≦c1≦1.5%.
[0046] The above M and A each contain one or more metal elements, and the selection of M and A can be the key to producing a metallic material composed of the above intrinsic alloy powder and cladding. During the solidification process of the alloy melt, no intermetallic compound composed of the main element of M and the main element of A is formed, and the above intrinsic alloy powder M a1 A b1 T c1 and covering A b2 T c2 In order for M to be generated, the following relationship must be satisfied for M and A:
[0047] M which does not form one or more intermetallic compounds between M and A 1 -A 1 This includes combinations of elements, where M 1 represents any element in M, and A 1 represents any element in A, and the main element in M is M 1 -A 1 Each M that satisfies the element combination conditions 1 It is composed of elements, and the main element of A is M 1 -A 1 Each A that satisfies the element combination conditions 1 It is composed of elements.
[0048] Furthermore, in M or A, each M that satisfies the above combination condition 1 Element or each A 1 If the atomic percentage content of an element is greater than 30% of M or A, it can be referred to as a major element of M or A, respectively.
[0049] Furthermore, when the above M includes at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, Co, Ni, Mn, Cu, and Ag, and A includes at least one of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Mg, Ca, Li, Na, K, In, Pb, and Zn, it can be ensured that an intermetallic compound consisting of the main element of M and the main element of A is not formed during the solidification process of the alloy melt. According to the alloy phase diagram, among the above elements, any element in M can be combined with the corresponding M which does not form an intermetallic compound. 1 -A 1 In A, combination pairs of Cr-Y, Ti-Ce, Fe-Mg, Co-K, Ni-Li, Mn-Mg, Cu-Li, Ag-Pb, etc. can be found. 1 -A 1 If there are combination pairs, each M 1 and each A 1 The group satisfies the condition that the corresponding intermetallic compounds are not formed when the alloy melt solidifies. For example, Ti-Ce, Ti-Gd, Nb-Ce, and Nb-Gd are all M 1 -A 1 If the combination pair condition is met, (Ti-Nb)-(Ce-Gd) still satisfies the combination condition that the corresponding alloy melt does not form intermetallic compounds during solidification, when the main elements of M include Ti and Nb, and the main elements of A include Ce and Gd.
[0050] In addition, the main element in M and the main element in A are M 1 -A 1 When one or more combination pairs of the above are satisfied, M is the main element M 1 Element M that can form a stable high melting point intermetallic compound with 2 If also included, M 1 and M. 2 M exists stably at a high melting point 1 -M 2 Forming intermetallic compounds, and M 1 and M. 2None of these elements form intermetallic compounds with the main element in A. In this case, the intrinsic alloy powder is M 1 -M 2 It is an intermetallic compound powder.
[0051] Preferably, M includes at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, and Ti, and A includes at least one of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu.
[0052] Preferably, when M contains at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, and Ti, and simultaneously contains at least one of Fe, Co, and Ni, a high melting point intermetallic compound can be formed between these two subclass elements of M, and when A contains at least one of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, an intrinsic intermetallic compound powder mainly composed of two subclass elements of M can be formed.
[0053] Preferably, the M includes at least one of the subclass elements W, Cr, Mo, V, Ta, Nb, Zr, Hf, and Ti, and at least one of the subclass elements Fe, Co, and Ni. When the molar ratio of the two subclass elements is about 1:1, a stable high melting point intermetallic compound can be formed between the two subclass elements of M. When A includes at least one of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, an intrinsic intermetallic compound powder mainly composed of the two subclass elements of M and having a molar ratio of about 1:1, and a coating mainly composed of the A element are formed during the solidification process of the alloy melt.
[0054] Preferably, M includes at least one of Mn, Fe, Ni, Cu, and Ag, and A includes at least one of Mg, La, In, Na, K, Li, and Pb.
[0055] Furthermore, the M includes at least one of Ir, Ru, Re, Os, Tc, W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, and Fe, and A includes at least one of Cu and Zn.
[0056] Supplementary explanation: Furthermore, the above M includes at least one of Ir, Ru, Re, Os, Tc, W, Cr, Mo, V, Ta, and Nb, and A includes Cu.
[0057] Furthermore, the above M contains at least one of Ir, Ru, Re, Os, and Tc, and A contains Cu.
[0058] It should be noted that the above A, M, or T may contain alloy elements or impurity elements other than the above elements. As long as the change in the content of these elements does not cause a "qualitative change" in the initial alloy solidification process and law, it will not affect the realization of the above technical solution of the present invention.
[0059] The present invention further relates to an alloy powder, the alloy powder being produced by removing the coating of a metallic material consisting of the intrinsic alloy powder and the coating, the elemental composition of which is mainly M. a3 A b3 T c3 a3, b3, c3 respectively represent the atomic percent contents of the corresponding element compositions, b3>0, a3+b3+c3=100%, and the content of T element in the alloy powder is higher than the content of T element in the intrinsic alloy powder, i.e. c3>c1>0.
[0060] The alloy powder is produced by removing the coating of the metal material composed of the endogenous alloy powder and the coating. Therefore, the properties of the alloy powder are almost the same as those of the endogenous alloy powder, but the difference is that the endogenous alloy powder is coated with the coating, which can prevent the influence of impurities such as oxygen in the environment, and when the alloy powder, especially the alloy powder has a finer particle size such as nano alloy powder, the atoms on the surface or surface layer of the alloy powder will combine with impurity elements such as oxygen during the exposure process, and the T element content will increase (i.e., c3>c1>0).
[0061] Preferably, the number of single crystal particles in the alloy powder accounts for 60% or more of the total number of particles.
[0062] More preferably, the number of single crystal particles in the alloy powder accounts for 75% or more of the total number of particles.
[0063] More preferably, the number of single crystal particles in the alloy powder accounts for 90% or more of the total number of particles.
[0064] Preferably, the grain size of the alloy powder is in the range of 3 nm to 10 mm.
[0065] Supplementary explanation: The particle size range of the above alloy powder is 3 nm to 1 mm.
[0066] Preferably, the grain size of the alloy powder is in the range of 3 nm to 500 μm.
[0067] Preferably, the grain size of the alloy powder is in the range of 3 nm to 99 μm.
[0068] Preferably, the grain size of the alloy powder is in the range of 3 nm to 25 μm.
[0069] Preferably, the grain size of the alloy powder is in the range of 3 nm to 10 μm.
[0070] Preferably, the grain size of the alloy powder is in the range of 3 nm to 5 μm.
[0071] The present invention further relates to a spherical or nearly spherical alloy powder, the spherical or nearly spherical alloy powder being obtained by subjecting the alloy powder to a plasma spheroidizing treatment, the elemental composition of which is mainly M a4 A b4 T c4 a4, b4, and c4 each represent the atomic percent content of the corresponding element composition, b4>0, a4+b4+c4=100%, and the content of the T element in the spherical or nearly spherical alloy powder is higher than the content of the T element in the alloy powder that has not been subjected to plasma spheroidizing treatment, i.e., c4>c3>c1>0.
[0072] Furthermore, by pre-pulverizing the selected particles using a jet mill prior to the plasma spheroidization treatment, particles that tend to become entangled can be dispersed and pulverized, which is advantageous for the subsequent spheroidization treatment.
[0073] Furthermore, the alloy powder is subjected to a sieving process prior to plasma spheroidization.
[0074] Furthermore, the particle size of the plasma spheroidized alloy powder is in the range of 5 μm to 200 μm.
[0075] Supplementary explanation: The particle size of the alloy powder subjected to the plasma spheroidizing treatment is in the range of 5 μm to 100 μm.
[0076] The present invention further relates to a method for producing a metallic material comprising an intrinsic alloy powder and a coating, the method comprising the steps of:
[0077] (1) M a0 A b0 T c0 The main element composition is M a0 A b0 T c0A process of melting an initial alloy melt, wherein both M and A contain one or more metallic elements, T is an impurity element containing oxygen, a0, b0, and c0 represent the atomic percentage contents of the corresponding compositional elements, and a0 + b0 + c0 = 100%, a0 + b0 + c0 = 100%, 0 < c0 ≤ 15%. One or more combinations of M1 - A1 elements that do not form intermetallic compounds are included between M and A. M1 represents any element among M, and A1 represents any element among A. Moreover, the main element of M is composed of M1 elements that satisfy the combination conditions of M1 - A1 elements, and the main element of A is composed of A1 elements that satisfy the combination conditions of M1 - A1 elements, and
[0078] (2)M a0 A b0 T c0 Solidifying the initial alloy melt into a solid state, and separating M from the melt a1 A b1 T c1 A dispersion particle phase and A that coats the dispersion particles b2 T c2 A step of obtaining a matrix phase, that is, a metallic material composed of the above-mentioned in - situ alloy powder and the coating. Here, 0 < c1 < c0 < c2, that is, M a0 A b0 T c0 The content of the T element in the initial alloy melt is higher than the content of the T element in the dispersion particle phase and lower than the content of the T element in the matrix phase for M a1 A b1 T c1 A b2 T c2 characterized by including the above steps.
[0079] As the solidification method of the above - mentioned initial alloy melt, methods such as ordinary casting, continuous casting, melt strip casting, melt extraction method, etc. can be mentioned. The particle size of the above - mentioned in - situ alloy powder is related to the solidification rate of the initial alloy melt. Generally speaking, the particle size of the in - situ alloy powder has a negative correlation with the solidification rate of the initial alloy melt, that is, the higher the solidification rate of the initial alloy melt, the smaller the particle size of the in - situ alloy powder.
[0080] Furthermore, the solidification method of the above-mentioned initial alloy melt does not include a solidification method corresponding to the atomization pulverization technology.
[0081] Supplementary explanation: The solidification rate range of the above initial alloy melt is 0.001K / s ~ 10 8 K / s.
[0082] Furthermore, the solidification rate range of the initial alloy melt is 0.001K / s to 10 7 K / s.
[0083] Furthermore, the particle size range of the intrinsic alloy powder is 3 nm to 10 mm.
[0084] Furthermore, the particle shape of the intrinsic alloy powder is not limited and may include at least one of branched, spherical, nearly spherical, square, discoid, and rod-shaped, and when the particle shape is rod-shaped, the particle size specifically refers to the diameter dimension of the cross section of the rod.
[0085] The shape of the metallic material composed of the intrinsic alloy powder and the coating is related to the solidification method. When the solidification method is continuous casting, the shape is generally slat-like, when the solidification method is melt stripping, the shape is generally strip-like or thin plate-like, when the solidification method is melt drawing, the shape is generally mainly thread-like. The faster the solidification rate, the thinner, finer and narrower the cross section of the metallic material composed of the intrinsic alloy powder and the coating is obtained, and conversely, the slower the solidification rate, the thicker, coarser and wider the cross section is.
[0086] Furthermore, the shape of the metallic material composed of the intrinsic alloy powder and the coating does not include the powder shape of the product corresponding to the atomized powder manufacturing technology.
[0087] Preferably, the initial alloy melt is solidified by a melt stripping method, and the solidification rate is 100K / s to 10 7 At K / s, a strip of metallic material consisting of endogenous alloy powder and cladding with a thickness of about 10 μm to 5 mm is obtained, with the particle size range of the endogenous alloy powder being 3 nm to 200 μm.
[0088] Preferably, when the initial alloy melt is solidified by a normal casting or continuous casting method and the solidification rate is 0.001 K / s to 100 K / s, a bulk metal material is obtained that is composed of an intrinsic alloy powder and a coating, and in which the particle size range of the intrinsic alloy powder is 200 μm to 10 mm and at least one dimension in a three-dimensional scale direction exceeds 5 mm.
[0089] Supplementary explanation: Furthermore, the metal material composed of the above-mentioned endogenous alloy powder and the coating body is in a band shape, and the thickness of the band is 5 μm to 5 mm.
[0090] Furthermore, the metal material composed of the intrinsic alloy powder and the coating is in the form of a strip, and the thickness of the strip is 10 μm to 1 mm.
[0091] Furthermore, the metal material composed of the intrinsic alloy powder and the coating is in the form of a strip, and the thickness of the strip is 10 μm to 500 μm.
[0092] Furthermore, the metal material composed of the intrinsic alloy powder and the coating is in the form of a strip, and the thickness of the strip is 10 μm to 100 μm.
[0093] Furthermore, the lower limit of the volume percentage content of the endogenous alloy powder in the metal material composed of the endogenous alloy powder and the coating body is 1%, and the upper limit is a volume percentage content corresponding to the requirement that the endogenous alloy powder can be dispersed in the coating body.
[0094] Preferably, the volume percentage content of the intrinsic alloy powder in the metal material composed of the intrinsic alloy powder and the coating is in the range of 5% to 50%.
[0095] More preferably, the volume percentage content range of the intrinsic alloy powder in the metal material composed of the intrinsic alloy powder and the coating is 5% to 40%, with the preferred lower limit ensuring economic efficiency and the preferred upper limit fully ensuring that the intrinsic alloy powder can be dispersed and distributed in the coating.
[0096] Preferably, the number of single crystal grains in said intrinsic alloy powder accounts for 60% or more of the total number of grains.
[0097] More preferably, the number of single crystal grains in the intrinsic alloy powder accounts for 75% or more of the total number of grains.
[0098] More preferably, the number of single crystal grains in the intrinsic alloy powder accounts for 90% or more of the total number of grains.
[0099] moreover, The above intrinsic alloy powder M a1 A b1 T c1 The melting point of The above-mentioned covering If this condition is met, when the initial alloy solidifies, the matrix phase solidifies last, covering the intrinsic alloy powder.
[0100] moreover, The above intrinsic alloy powder A element is dissolved in solid solution, that is, 0 <b1である。
[0101] Preferably, 0 <b1≦15%であり、すなわちM a1 A b1 T c1 The A element (atomic percent content) can be dissolved in 15% or less of M. a1 A b1 T c1 The solubility of A in intrinsic alloy powders also depends on the major element composition, impurity content, and solidification rate of a particular alloy melt. In general, if the melt solidifies faster and smaller intrinsic alloy powders such as nanopowder are formed, more A elements can be dissolved.
[0102] Supplementary explanation: In addition, 0.01% <b1≦15%である。さらに、0.05%<b1≦15%である。さらに、0.1%<b1≦15%である。さらに、0.1%<b1≦15%である。
[0103] Furthermore, T is an impurity element such as O, H, N, P, S, F, Cl, etc., including oxygen, and 0 <c1≦1.5%である。
[0104] Supplementary explanation: Furthermore, T is O, H, N, P, S, F, Cl elements including O, which are all non-metallic elements with similar properties. The present invention finds that the above T elements in the initial alloy melt have similar thermodynamic effects on the diffusion and phase distribution of A, M, and T elements in the matrix phase and dispersed particle phase during the solidification of the initial alloy melt. Due to this thermodynamic effect, when the T content is high, more A elements are mixed with M. a1 A b1 T c1 It can be dissolved in the intrinsic alloy powder. The reason is that the A, M, and T elements in the initial alloy melt are initially mixed uniformly, and during the cooling and solidification process of the initial alloy melt, the dispersed particle phase mainly composed of M will first precipitate from the melt, and the T-type element atoms will be released during the precipitation process. When the T-type element atoms are released, a certain type of vacancy may be formed, and this vacancy can be replaced by M-type atoms and also by A-type atoms. Therefore, under the same circumstances, the higher the content of T element, the more vacancies can be replaced, and the more M a1 A b1 T c1 The content of A elements dissolved in the intrinsic alloy powder is also high. Therefore, in addition to the influence of the main element composition of the initial alloy melt, M a1 A b1 T c1 The content of A elements dissolved in the intrinsic alloy powder is also affected by the thermodynamics and kinetics during the solidification process of the initial alloy melt. From the viewpoint of thermodynamics, when the T content is high, more A elements are dissolved in M. a1 A b1 T c1 From the viewpoint of kinetics, if the solidification rate of the initial alloy melt is high and smaller intrinsic alloy powder is formed, more A elements can be added to M. a1 A b1 T c1 It can be dissolved in the intrinsic alloy powder.
[0105] Furthermore, the above M a0 A b0 T c0The initial alloy melt is smelted from an alloy feedstock comprising a first feedstock and a second feedstock, where the main element composition of the first feedstock is M d1 T e1 The main element composition of the second raw material is A d2 T e2 where d1, e1, d2, and e2 represent the atomic percent content of the corresponding elemental composition, and 0 <e1≦10%、0<e2≦10%、d1+e1=100%、d2+e2=100%である。
[0106] Preferably, 0 <c0≦10%、0<e1≦7.5%、0<e2≦7.5%である。
[0107] More preferably, 0.01%≦c0≦10%, 0.01%≦e1≦7.5%, and 0.01%≦e2≦7.5%.
[0108] This shows that a metal material consisting of an intrinsic alloy powder containing a high-purity target intrinsic alloy powder and a cladding can be produced from raw materials of low purity.
[0109] Supplementary explanation: In various embodiments, the metallic material comprising the intrinsic alloy powder and the coating may further include: endogenous alloy powder The T impurity content in 1. The endogenous M a1 A b1 T c1 The content of T impurities in the alloy powder is 1. It is lower than the T content in the raw material, that is, c1 is smaller than e1.
[0110] Supplementary explanation: In addition, in various embodiments, in the metal material composed of the intrinsic alloy powder and the coating, the intrinsic M a1 A b1 T c1 The volume percentage content of the alloy powder corresponds to the volume percentage content of the first raw material when the raw material is prepared. Corresponding means that it is almost the same. Therefore, the intrinsic M in the metal material composed of the target intrinsic alloy powder and the cladding body is a1 A b1 Tc1 Depending on the percentage content of the alloy powder, M a0 A b0 T c0 When smelting the initial alloy melt, 1. raw materials and Second the required volume percentage content of each raw material can be roughly estimated. 1. raw materials and Second Once the volume percentage content of each raw material is determined, the relative ratio of a0 to b0 can be calculated from data such as the atomic weight and density of each element.
[0111] Note that since impurity elements such as O in the atmosphere may be mixed into the melt during the smelting process, c0>e1 and c0>e2 may occur. That is, M a0 A b0 T c0 the impurity content in the initial alloy melt of increases relative to the total impurity content in the alloy raw materials.
[0112] Supplementary explanation: At the same time, during the melting process of the initial alloy, some T elements may form a small amount of slag on the surface of the melt together with M or A. Since the slag is generally solid and does not belong to the initial alloy melt, the T element content in the initial alloy melt may also be c0<e1 and c0<e2. That is, M a0 A b0 T c0 the impurity content in the initial alloy melt of decreases relative to the total impurity content in the alloy raw materials.
[0113] The present invention further relates to a method for manufacturing alloy powder. The method for manufacturing the alloy powder is characterized by removing the coating part in the metal material composed of the above-mentioned intrinsic alloy powder and the coating while retaining the intrinsic alloy that cannot be removed.
[0114] Furthermore, as a method for removing the coating and retaining the intrinsic alloy powder, at least one of removal by acid solution dissolution reaction, removal by alkali solution dissolution reaction, vacuum volatilization removal, and natural oxidation and pulverization removal of the coating can be mentioned.
[0115] When using an acidic solution for reactive removal, select an appropriate acid type and concentration. The selection criteria are as follows: covering becomes an ion and enters the solution, endogenous alloy powder The aim is to ensure that the coating does not react significantly with the corresponding acid to effect removal of the coating.
[0116] Additionally, the acid solution is degassed to reduce dissolved oxygen and nitrogen content.
[0117] When using an alkaline solution for reactive removal, select the appropriate type and concentration of the alkaline. The selection criteria are as follows: covering becomes an ion and enters the solution, endogenous alloy powder The aim is to ensure that the coating is hardly reacted with the corresponding alkali and thus achieves removal of the coating.
[0118] Additionally, the alkaline solution is degassed to reduce the dissolved oxygen and nitrogen content.
[0119] When removing by vacuum evaporation, select appropriate vacuum and temperature conditions. The selection criteria are: covering is volatile and has a high melting point endogenous alloy powder The object of the present invention is to ensure that the coating is retained without volatilization and to effect removal of the coating.
[0120] When the coating is very susceptible to natural oxidation and powdering, it is possible to remove the naturally oxidized and powdered coating in advance and then completely remove the coating by another method.
[0121] Supplementary explanation: Furthermore, in one embodiment, M contains Fe, A contains La, and the metal material composed of the endogenous alloy powder and the coating is a metal ribbon composed of the endogenous Fe alloy powder and the La coating, La is solid-dissolved in the endogenous Fe alloy powder, the endogenous Fe alloy powder is pre-separated from the matrix La oxide powder by natural oxidation-pulverization of the La coating, and the Fe alloy powder is separated from the matrix La oxide using a magnetic field due to the magnetic properties of the Fe alloy powder.
[0122] The invention further relates to applications of the alloy powders in powder metallurgy, metal injection molding, magnetic materials and coatings.
[0123] Furthermore, when the grain size of the alloy powder is large, it can be used in the fields of powder metallurgy and metal injection molding; when the grain size of the alloy powder is small, such as in the nanoscale, it can be mainly used in the field of paints as a paint additive with special functions.
[0124] Furthermore, when the alloy powder is a soft magnetic alloy powder, it can also be used in the field of magnetic materials.
[0125] The present invention further relates to applications of the spherical or near-spherical alloy powders in powder metallurgy, metal injection molding and metal powder 3D printing.
[0126] The present invention further relates to the application of metallic materials comprising intrinsic alloy powders and coatings in coatings and composite materials.
[0127] Furthermore, a metal material composed of an endogenous alloy powder having an average particle size of less than 1000 nm and a coating is selected, the coating is removed, and the obtained alloy powder is mixed with other components of a paint or composite material simultaneously with or immediately after the removal of the coating so as to reduce the content of impurities including O newly introduced on the powder surface or surface layer after the surface of the alloy powder is exposed, thereby obtaining an alloy powder with high surface activity, and the other components of the paint or composite material are well bonded to the surface of the alloy powder on an atomic scale, thereby obtaining a paint or composite material to which a high-purity, high-activity alloy ultrafine powder has been added, which can be used in various fields such as antibacterial coating, weather-resistant coating, stealth coating, radio wave absorbing coating, abrasion-resistant coating, corrosion-resistant coating, and resin-based composite materials.
[0128] Furthermore, after the coating is removed, the steps of washing, drying, and mixing the alloy powder with the other components of the paint or composite are all carried out in a vacuum environment or protective atmosphere.
[0129] Furthermore, after the coating is removed, the resulting alloy powder is mixed with paint or other components of the composite material within 20 minutes.
[0130] More preferably, after the coating is removed, the resulting alloy powder is mixed with the paint or other components of the composite within 5 minutes.
[0131] In summary, the technical solution described in the present invention has the greatest advantage that in the process of forming alloy powder, the alloy powder is refined and simultaneously solid-solution alloyed, and the invention of a metal material composed of high-purity intrinsic alloy powder and a coating also provides a new idea for the production, storage and use of high-purity alloy powder.
[0132] Supplementary explanation: The present invention uses the basic concept of selective etching in principle, but is fundamentally different from the selective etching of the dealloying method. Specifically, the precursor alloy selected by the dealloying method must be a single amorphous phase, or one or more intermetallic phases, or a mixture of one or more intermetallic phases and an amorphous phase. Before the dealloying reaction, the target atoms are uniformly dispersed in each phase of the alloy in the form of atoms (regardless of whether it is an intermetallic phase or an amorphous phase, the target atoms do not aggregate with other target atoms to form a target phase). After the dealloying reaction, the active atoms are etched, the target atoms are dissociated, and are gathered by rediffusion rearrangement to form a nanoporous structure. Therefore, the products produced by the dealloying method are generally not powder materials but nanoporous materials, and the macroscopic shape of the material is almost unchanged before and after the dealloying reaction. That is, the shape of the alloy ribbon is still a nanoporous ribbon after the alloying reaction, and the shape of the alloy block is still a nanoporous block after the dealloying reaction (as shown in the literature Generalized fabrication of nanoporous metals (Au, Pd, Pt, Ag and Cu) through chemical dealloying, J. Phys Chem C. 113 (2009) 12629-12636). Only if ultrasound or other destructive methods are applied, the obtained nanoporous structure can be further broken down into loose nanoporous fragments or nanoparticles. Only if ultrasound or other destructive methods are applied, the obtained nanoporous structure can be further broken down into loose nanoporous fragments or nanoparticles.
[0133] However, the present invention provides a method for producing a bulk first raw material by selecting a special alloy component pair. Second The raw materials are heated above the melting point of the two raw materials to form M a0 A b0 T c0 During the solidification process of the initial alloy melt, the element composition becomes mainly M a1 A b1 T c1 A dispersed particle phase with elemental composition mainly A precipitates outside the melt. b2 T c2The matrix phase, which is 0.1 to 1.0 μm, eventually solidifies and covers the dispersed particle phase, which can become nanoparticles if the cooling rate is fast enough, submicron particles if the cooling rate is slower, micron particles if the cooling rate is still slower, and millimeter-sized particles if the cooling rate is still slower. a1 A b1 T c1 The intrinsic alloy powder is formed during solidification of the initial alloy melt, rather than through a process such as acid reaction stripping, and subsequent stripping is simply a matter of removing the coating to yield freely dispersed alloy nanoparticles.
[0134] Specifically, the present invention has the following beneficial effects:
[0135] First, it realizes the production of high purity intrinsic alloy powder from low purity raw materials, which points out a new route for producing high purity metal powder materials from low purity raw materials and has positive significance. The improvement of the purity of the high purity intrinsic alloy powder of the present invention is mainly achieved through the following two mechanisms:
[0136] 1) "Absorption" effect of A element on impurity elements. The selected A element has a lower melting point and higher activity than the M element, so it has a stronger affinity with the impurity element T than the M element. This causes more of the T impurity element to enter the matrix phase mainly composed of A elements, or to form slag with the A element in the molten state, and then to be separated and removed together with the alloy melt. For example, this type of process is possible when the A element contains rare earth elements or calcium elements, which have a high affinity with oxygen.
[0137] 2) During the nucleation and growth process of the intrinsic alloy powder (intrinsically precipitated dispersed particle phase), the impurity elements are discharged into the remaining melt. Unless the intrinsic alloy powder precipitates later than the matrix phase during the solidification process, the impurities are enriched in the melt of the part that solidifies last, that is, the part that is mainly composed of A elements and solidifies to form the matrix phase.
[0138] Second, M a1 A b1 T c1During the process of nucleation, growth and refinement of the intrinsic alloy powder, the A element, which cannot form an intermetallic compound with M in the intrinsic alloy powder, is simultaneously formed into a solid solution alloy. The solid solution alloying brings positive effects.
[0139] By way of example, M produced from raw materials containing relatively high levels of impurity elements a1 A b1 T c1 It was found that the intrinsic alloy powders tended to have a significant amount of A in solid solution. a1 A b1 T c1 The solid solubility of A in the intrinsic alloy powder of also varies with the differences in the main element composition, impurity content and solidification rate of a particular alloy melt. In general, in the determined MAT alloy melt, when the T content is high, the melting and solidification rate is high, and smaller intrinsic alloy powders such as nanopowder are formed, the M a1 A b1 T c1 Intrinsic alloy powder can dissolve many A elements. a1 A b1 T c1 The solid solution of the A element in the endogenous alloy powder allows the endogenous alloy powder to have some properties of solid solution alloyed powder, which has positive significance.
[0140] In addition, M a1 A b1 T c1 The solid solution alloying of A elements in intrinsic alloy powders is the result obtained when the corresponding initial alloy melt contains sufficient A elements (most of the other A elements are dissolved in the matrix phase A). b2 T c2(formed by YO3O3), which is completely different from the situation of directly adding a small amount of A element to M to obtain MA alloy. For example, in the industry, a small amount of Y (such as 0.3wt%) is generally added to Ti metal to improve the strength and plasticity of Ti-Y alloy (Supplementary explanation: equivalent to the atomic percentage content of Y of 0.16at%). The mechanism is that after a small amount of Y is added to Ti metal, it generally combines with impurity elements such as O in Ti metal to form Y2O3 oxide, and the existence of Y2O3 oxide acts as a mass point of heterogeneous nuclei, increasing the nucleation rate and obtaining finer crystal grains during the solidification process of Ti metal, and by the principle of refining crystal grains, the strength and plasticity of Ti metal can be improved at the same time. This kind of alloying is not alloying in the strict sense because a small amount of Y is added to Ti metal that is not of absolute purity and then exists in the form of Y2O3 oxide. The present invention can obtain a Ti-YT alloy melt by smelting a Ti raw material containing impurity T and a Y raw material containing impurity T, and after solidifying the alloy melt, a Ti-YT intrinsic alloy powder containing a small amount of Y in solid solution can be obtained. Here, Y is the actual alloying element involved in solid solution alloying. This difference can enable the Ti-YT intrinsic alloy powder to obtain obviously different beneficial application effects. For example, when the Ti-YT alloy fine powder after the removal of the coating matrix phase and spheroidization is used in the field of metal 3D printing, in the laser remelting process of the powder, the "stored" solid solution Y element in the Ti-YT alloy powder can absorb the O element (introduced in the process of removing the coating matrix phase and spheroidizing) on the surface or surface layer of the Ti-YT alloy powder to form Y2O3 oxide. By using Y2O3 oxide as a heterogeneous formation nucleus, the grains in the Ti-YT alloy structure after laser remelting and solidification can be significantly refined, and the strength and plasticity of the 3D printing device can be improved. On the other hand, in the Ti-Y powder produced by the conventional atomized powder production of Ti-Y alloy, Y has already combined with O to form Y2O3 oxide, and new O is introduced into the powder during the production process, so there is no “free” Y to further combine with O during the powder laser remelting process.Alternatively, to achieve this goal, it is necessary to add Y to the conventional Ti-Y alloy powder in order to allow some "free" Y to be dissolved in the Ti-Y alloy powder in addition to the Y2O3 oxide, which obviously does not reach the excellent performance of the Ti-YT alloy powder of the present invention in which only Y element is dissolved.
[0141] Third, an alloy powder mainly composed of single crystal particles is obtained. Compared with polycrystalline powder, single crystal powder has many significant and beneficial effects. During the solidification process of the initial alloy melt, each endogenous dispersed particle is nucleated at a certain position in the melt and then grows according to a specific atomic arrangement. When the volume percentage content of the matrix phase is controlled to allow each endogenous particle to be dispersed, it is difficult for each endogenous particle to grow together. Therefore, the finally obtained dispersed particle phase is mostly a single crystal phase. Even if the scale of the dendrite particles is several tens of microns, the growth direction of each secondary dendrite maintains a certain phase relationship with the growth direction of the main dendrite, and still belongs to a single crystal particle.
[0142] For polycrystalline materials, the grain boundaries are generally prone to contain impurity elements released from within the crystal during the solidification process, making it very difficult to obtain high-purity polycrystalline powder materials. In addition, if the powder material is mainly composed of single crystal particles, its purity is guaranteed. In addition, the atoms on the surface of the single crystal particles have a specific arrangement, such as the (111) plane arrangement, and these specific arrangements give the single crystal powder material special mechanical, physical and chemical properties, which can produce beneficial effects.
[0143] Fourth, the intrinsic alloy powder and the coating are used in the metal material, and the intrinsic alloy powder is surrounded by the matrix phase formed in situ, thereby maintaining the high purity and activity of the intrinsic aluminum alloy powder. Metal or alloy powders produced by conventional chemical and physical methods, especially nanopowder with a very large specific surface area, are very prone to oxidation naturally, and thus the powder is difficult to store. To solve this problem, the present invention uses the coating as it is to protect the intrinsic alloy powder after producing the metal material composed of the intrinsic alloy powder and the coating, rather than hastily removing the coating and using other means to prevent the intrinsic alloy powder from being contaminated by impurities such as oxygen. Such a metal material composed of the intrinsic alloy powder and the coating can be directly used as a raw material in downstream production. When the endogenous alloy powder needs to be used in downstream production, the endogenous alloy powder is released from the coating by the acid solution at a suitable time and under a suitable environment according to the characteristics of the following processes, and the released endogenous alloy powder is allowed to enter the next production process within the shortest possible time, greatly reducing the possibility of the endogenous alloy powder being contaminated by impurities such as oxygen. For example, when the endogenous alloy powder is a nanopowder, the alloy powder can be compounded with a resin at the same time or immediately after it is released from the coating, to produce a resin-based composite material with the highly active nano alloy powder added thereto.
[0144] Fifth, by controlling the solidification rate of the initial alloy melt, the production of intrinsic alloy powders with different continuous particle sizes can be realized, including the production of nanopowder, submicron powder, micron powder, and even millimeter-sized powder. Compared with the traditional top-down (by crushing blocks into small particles) or bottom-up (by agglomerating atoms into large particles) physical or chemical methods, the "primary grain phase precipitation-déphasing method" of the present invention is a completely new method for producing powder materials with particle sizes ranging from nanometers to millimeters.
[0145] Supplementary explanation: In the field of powder material production, nanoparticles of a few nanometers or tens of nanometers can be easily produced from the atomic or ionic scale by bottom-up methods (such as ion reduction), and micron particles of tens of microns can be easily prepared by top-down methods (such as ball milling). However, it is too difficult to grow from atoms to the 1 μm level, and it is also very difficult to break down bulk materials from the top to the 1 μm level, so it is difficult to produce powder materials with a thickness of about 1 μm, whether by bottom-up or top-down. Traditional methods for producing powder materials are only suitable for certain particle size ranges, such as ion reduction to produce nanoparticles less than 100 nm and atomization to produce micron particles greater than 10 μm. However, the method according to the present invention is very suitable for producing powder materials from a few nanometers to a few millimeters, and only requires controlling the solidification speed of the initial alloy melt, which can brilliantly solve the difficulty of producing powder materials with a particle size of about 1 μm.
[0146] In particular, the present invention is also particularly suitable for the large-scale, low-cost production of some special nanometal powders, such as nano-Ti powder. Due to the special nature of the Ti element, it is difficult to produce Ag, as well as Ag and Cu. + or Cu 2+ It is difficult or impossible to produce nano Ag or Cu by chemical reduction. Generally, nano Ti powder can only be produced in small batches by physical methods such as explosion method, and the cost is very high. Even if nano Ti powder is very useful, its industrial application is greatly limited because it costs several thousand yuan per kilogram. Therefore, the present invention ingeniously solves the large-scale, low-cost production of high-purity solid-solution alloyed nano Ti powder from low-purity raw materials, and is of immeasurable value.
[0147] Sixth, supplementary explanation: By ingeniously designing the combination of AM elements, using low-purity A and M raw materials, and at the same time making good use of the thermodynamic effects of T-type elements (O, H, N, P, S, F, Cl), especially the required characteristic O element, on A, M, and T elements during the solidification process of the MAT initial alloy melt, not only can the purification of T in the MAT intrinsic alloy powder be realized, but also a significant increase in the solid solution amount of A in the MAT intrinsic alloy powder can be cleverly realized.
[0148] Seventh, Supplementary Explanation: In the present invention, M and A do not form one or more intermetallic compounds. 1 -A 1 This includes the combination of elements. To meet this important requirement, careful design is required in the selection of alloy composition. 1 -A 1 The solidification structure of the combination of elements is M 1 -A 1It does not form an intermetallic compound, and the above A contains at least one of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Mg, Ca, Li, Na, K, In, Pb, Zn, and Cu. There seem to be many elements listed above, but Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu are all rare earth elements, and when the rare earth elements are replaced by RE, A contains only at least one of RE, Mg, Ca, Li, Na, K, In, Pb, Zn, and Cu. Among them, RE, Mg, Ca, Li, Na, K, In, Pb, and Zn are metal elements with very high activity, very low melting point, or very soft, and are usually not alloyed with other elements to improve strength or corrosion resistance (alloys formed with M have no effect because A is a coating), and are generally rarely used and are not popular as academic research and industrial application elements. However, Cu is rarely alloyed with the unpopular precious metals Ir, Ru, Re, Os, and Tc, and even when alloyed with W, Cr, Mo, V, Ta, and Nb, the corresponding materials are generally obtained by mixing and sintering Cu powder with W, Cr, Mo, V, Ta, and Nb powders using powder metallurgy. Therefore, the M selected by the present invention is 1 -A 1 The combination of elements is an unpopular combination of elements that is rarely involved in academia and industry, however, the present invention has turned the disadvantages of the unpopular combination of elements into advantages and creatively found a new way to apply it in the field of powder material manufacturing.
[0149] The present invention makes good use of the characteristics of the above unpopular element combinations, and realizes the production of metal materials composed of intrinsic alloy powder and coating by utilizing the phenomenon of separation of A and M during the solidification process of the alloy, the initial precipitation of primary crystal particles dominated by M, and the subsequent precipitation of a matrix phase mainly composed of A. However, elements such as RE, Mg, Ca, Li, Na, K, In, Pb, and Zn are very active, or have very low melting points, or are very soft, so it is convenient to remove the coating composed of these elements. Therefore, it is obviously of positive significance to realize the production of alloy powder by cleverly using the above unpopular element combinations.
[0150] Therefore, the present invention creatively adopts low-purity raw materials, integrates multiple beneficial technical solutions such as the generation of single crystal alloy powder, the purification and preservation of alloy powder, and powder solid-solution alloying, and realizes the production of high-purity nanoscale, submicron scale, micron scale and millimeter scale solid-solution alloy powder, which has good application prospects in the fields of catalysis, powder metallurgy, composite materials, magnetic materials, sterilization, metal injection molding, metal powder 3D printing, paints, composite materials and other fields. [Brief description of the drawings]
[0151] [Figure 1] FIG. 1 is a localized backscattered SEM photograph of the intrinsic nano Ti alloy powder and Gd coating of Example 3 of the present invention.
[0152] [Diagram 2] FIG. 2 is a SEM photograph of the nano Ti alloy powder of Example 3 of the present invention.
[0153] [Diagram 3] FIG. 3 is a localized backscattered SEM photograph of the intrinsic Ti—Co dendritic alloy powder and Gd coating of Example 6 of the present invention.
[0154] [Figure 4] FIG. 4 is a SEM photograph of the Ti—Co dendritic alloy powder of Example 6 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0155] The present invention will be further described below with reference to specific examples. Note that the examples described below are intended to facilitate understanding of the present invention, but are not intended to limit the present invention in any way.
[0156] [Example 1] This embodiment provides a metal ribbon composed of intrinsic nano Ti alloy powder and Ce cladding, a nano Ti alloy powder, and its manufacturing method and application, which includes the following steps:
[0157] (1) Low-purity titanium containing Cl, N, O, and H with weight percentages of 0.3wt%, 0.1wt%, 0.3wt%, and 0.03wt%, respectively, was selected. When converted to atomic percent content, the atomic percent contents of Cl, N, O, and H are 0.4at%, 0.33at%, 0.88at%, and 1.39at%, respectively, and the total content is 3at%. Low-purity rare earth Ce containing 0.3wt% O was selected. When converted to atomic percent content, the O content of Ce is 2.57at%. Since Ti-Ce is an element combination pair that does not form an intermetallic compound and Ti has a higher melting point than Ce, Ti alloy powder can be manufactured based on this element combination pair.
[0158] For ease of calculation, other trace elements that may exist in the raw materials were used as the main elements, and the low-purity Ti raw material and the low-purity Ce raw material were mixed in a volume ratio of 1:3. According to the element density and atomic weight data, the composition of the alloy raw material was about (Ti) in atomic percentage content. 97 Cl 0.4 N 0.33 O 0.88 H 1.39 ) 39 (Ce 97.43 O 2.57 ) 61 Specifically, Ti 37.83 Ce 59.435 Cl 0.156 N 0.129 H 0.54O 1.91 The total content of Cl, N, H, O and other impurity elements T was approximately 2.735 at%.
[0159] (2) The above low-purity alloy raw material is induction melted to have a composition of about Ti 37.83 Ce 59.435 T 2.735 (T represents impurity elements such as Cl, N, H, and O) of the initial alloy melt was obtained. Some of the impurity elements in the initial alloy melt may become slag and be separated from the melt, reducing the impurity content, but some impurities in the environment and atmosphere, such as oxygen, may also enter the melt and increase the impurity content in the melt.
[0160] (3) The initial alloy melt was rapidly solidified into a ribbon with a thickness of about 100 μm by a copper roller strip casting method, and during the solidification process, a dispersed particle phase mainly composed of Ti was embedded in a matrix phase mainly composed of Ce and precipitated, resulting in a metallic ribbon composed of endogenous nano Ti alloy powder and Ce coatings. Here, the atomic percentage composition of the endogenous Ti alloy powder was about Ti. 99.1 Ce 0.5 T 0.4 The Ti alloy powder was composed mainly of single crystal particles with a particle size range of 3 nm to 300 nm. A small amount of Ce was dissolved in the endogenous Ti alloy powder, and the content of T impurities in the powder was significantly reduced compared to the low-purity Ti raw material, while other T impurities were enriched in the Ce coating. In the obtained metal ribbon composed of the endogenous nano-Ti alloy powder and the Ce coating, the volume percentage content of the endogenous Ti alloy powder was equivalent to the volume percentage content of the Ti raw material at the time of raw material preparation, and was still about 25 vol%, ensuring the dispersion distribution of the Ti alloy powder in the matrix phase mainly composed of Ce.
[0161] (4) The Ce coating in the metal ribbon composed of the endogenous nano Ti alloy powder and the Ce coating was removed using a dilute hydrochloric acid solution, and since the Ti alloy powder does not react with the dilute hydrochloric acid solution, the Ti-Ce-T alloy powder was obtained after separation, washing, and drying. Due to the adsorption of impurities such as oxygen on the surface layer and surface atoms of the exposed Ti-Ce-T alloy powder, the content of T impurities in the obtained Ti-Ce-T alloy powder was higher than that of the endogenous Ti-Ce-T alloy powder.
[0162] After step (3), step (5) may be carried out directly.
[0163] (5) The Ce coating in the metal ribbon, which is composed of endogenous nano-Ti alloy powder and Ce coating, was removed using a dilute hydrochloric acid solution from which dissolved oxygen had been removed. Within 20 minutes, the Ti alloy powder was separated in a protective atmosphere and mixed with epoxy resin and other paint components to produce a titanium alloy nano-modified polymer anticorrosive paint.
[0164] [Example 2] This embodiment provides a metal sheet composed of endogenous micron Ti alloy powder and Ce cladding, a micron Ti alloy powder, and its manufacturing method and application, which includes the following steps:
[0165] (1) Low-purity titanium containing Cl, N, O, and H with weight percentages of 0.3wt%, 0.1wt%, 0.3wt%, and 0.03wt%, respectively, was selected. When converted to atomic percent content, the atomic percent contents of Cl, N, O, and H are 0.4at%, 0.33at%, 0.88at%, and 1.39at%, respectively, and the total content is 3at%. Low-purity rare earth Ce containing 0.3wt% O was selected. When converted to atomic percent content, the O content of Ce is 2.57at%. Since Ti-Ce is an element combination pair that does not form an intermetallic compound and Ti has a higher melting point than Ce, Ti alloy powder can be manufactured based on this element combination pair.
[0166] For ease of calculation, other trace elements that may exist in the raw materials were used as the main elements, and the low-purity Ti raw material and the low-purity Ce raw material were mixed in a volume ratio of 1:3. According to the element density and atomic weight data, the composition of the alloy raw material was about (Ti) in atomic percentage content. 97 Cl 0.4 N 0.33 O 0.88 H 1.39 ) 39 (Ce 97.43 O 2.57 ) 61 Specifically, Ti 37.83 Ce 59.435 Cl 0.156 N 0.129 H 0.54 O 1.91 The total content of Cl, N, H, O and other impurity elements T was about 2.735 at%.
[0167] (2) The above low-purity alloy raw material is induction melted to have a composition of about Ti 37.83 Ce 59.435 T 2.735 (T represents impurity elements such as Cl, N, H, and O) of the initial alloy melt was obtained. Some of the impurity elements in the initial alloy melt may become slag and separate from the melt, reducing the impurity content, but some impurities in the environment and atmosphere, such as oxygen, may also enter the melt, increasing the impurity content in the melt.
[0168] (3) The initial alloy melt was solidified into a thin plate with a thickness of about 4 mm. During the solidification process, the mesodendritic dispersed particle phase, mainly composed of Ti, was embedded and distributed in the matrix phase, mainly composed of Ce, to obtain a thin metal plate composed of endogenous micron Ti alloy powder and Ce coating. Here, the atomic percentage composition of the endogenous Ti alloy dendritic powder was about Ti. 99.4 Ce 0.3 T 0.3The Ti alloy powder was mainly composed of single crystal dendritic particles with a particle size range of 1 μm to 150 μm. A small amount of Ce was dissolved in the endogenous Ti alloy powder, and the content of T impurities in it was significantly reduced compared to the low purity Ti raw material, and other large amounts of T impurities were enriched in the Ce coating. In the obtained metal sheet composed of the endogenous micron Ti alloy powder and the Ce coating, the volume percentage content of the endogenous Ti alloy powder was equivalent to the volume percentage content of the Ti raw material during the raw material preparation, which was still about 25 vol%, ensuring the dispersion distribution of the Ti alloy dendritic powder in the matrix phase mainly composed of Ce.
[0169] (4) The Ce coating in the metal sheet, which is composed of endogenous micron Ti alloy powder and Ce coating, was removed by dilute hydrochloric acid solution. Since the Ti alloy dendrite powder does not react with dilute hydrochloric acid solution, after separation, washing and drying, Ti-Ce-T alloy dendritic powder was obtained.
[0170] (5) The Ti-Ce-T alloy dendritic powder was jet-milled to disperse the entangled dendritic particles during the solidification process, while breaking down the large dendritic particles into smaller dendritic fragments.
[0171] (6) The Ti alloy dendritic powder obtained above was screened, and Ti alloy dendritic powder having a particle size range of 15 μm to 53 μm was selected. Then, a spherical or nearly spherical Ti alloy powder having little change in the particle size range was obtained by plasma spheroidization treatment.
[0172] (7) The obtained spherical or nearly spherical Ti alloy powder can be used in the 3D metal printing field.
[0173] [Example 3] This embodiment provides a metal ribbon composed of intrinsic nano Ti alloy powder and Gd coating, a nano Ti alloy powder, and a manufacturing method thereof, which includes the following steps:
[0174] (1) We selected a low-purity Ti raw material, both of which contain approximately 3 at% of the impurity T, and a rare earth raw material whose main component is Gd. Ti-Gd is an element combination pair that does not form an intermetallic compound, and Ti has a higher melting point than Gd, so Ti alloy powder can be produced based on this element combination pair.
[0175] (2) Low-purity Ti raw material and rare earth raw material mainly composed of Gd are mixed in a volume ratio of 15:85, and the alloy raw material is induction melted to obtain an alloy with an atomic percentage composition of about Ti 24 Gd 73 An initial alloy melt was obtained, which was T3 and had a T content of about 3 at %.
[0176] (3) The initial alloy melt was rapidly solidified into a ribbon with a thickness of about 100 μm by a copper roller strip casting method. During the solidification process, the dispersed particle phase mainly composed of Ti was embedded and distributed in the matrix phase mainly composed of Gd, resulting in a metallic ribbon composed of endogenous nano Ti alloy powder and Gd coatings. Figure 1 shows the microtopography of the metallic ribbon. Here, the atomic percentage composition of the endogenous Ti alloy powder is about Ti. 99.2 Gd 0.5 T 0.3 It was mainly composed of Ti nano single crystal particles with a small amount of Gd dissolved therein, with a particle size range of 3 nm to 300 nm. A large amount of other T impurities were enriched in the Ce coating, and the content of T impurities in the intrinsic Ti alloy powder was significantly reduced compared to the low-purity Ti raw material. As shown in Figure 1, in the obtained metal ribbon composed of the intrinsic nano Ti alloy powder and the Gd coating, the volume percentage content of the intrinsic Ti alloy powder was equivalent to the volume percentage content of the Ti raw material during the raw material preparation, which was still about 25 vol%, ensuring the dispersion distribution of the Ti alloy powder in the matrix phase mainly composed of Gd.
[0177] (4) The Gd coating in the metal ribbon, which is composed of endogenous nano Ti alloy powder and Gd coating, was removed by dilute hydrochloric acid solution. Since the Ti alloy powder does not react with the dilute hydrochloric acid solution, after separation, washing and drying, the Ti-Gd-T alloy powder shown in Figure 2 was obtained, and the particle size range was 3 nm to 300 nm.
[0178] [Example 4] The present embodiment provides a metal ribbon composed of intrinsic nano Ti-Nb-V alloy powder and Ce-La-Nd-Pr coating, a nano Ti-Nb-V alloy powder, and a manufacturing method thereof, which includes the following steps:
[0179] (1) Low-purity Ti, Nb, and V raw materials, each with an impurity T content of approximately 3 at%, and mixed rare earth raw materials mainly composed of Ce, La, Nd, and Pr were selected. Ti-Ce, Ti-La, Ti-Nd, Ti-Pr, Nb-Ce, Nb-La, Nb-Nd, Nb-Pr, V-Ce, V-La, V-Nd, and V-Pr are element combination pairs that do not form intermetallic compounds, and the melting points of Ti, Nb, and V are higher than those of Ce, La, Nd, and Pr, so Ti alloy powder can be produced based on these element combination pairs.
[0180] (2) Low-purity Ti, Nb, and V raw materials were mixed with mixed rare earth raw materials mainly composed of Ce, La, Nd, and Pr in a volume ratio of 1:2, and the alloy raw materials were induction melted to obtain an initial alloy melt of (Ti-Nb-V)-(Ce-La-Nd-Pr)-T with a T content of approximately 3 at%.
[0181] (3) The initial alloy melt was rapidly solidified into a ribbon with a thickness of about 100 μm by copper roller strip casting, and during the solidification process, the dispersed particle phase mainly composed of Ti-Nb-V was embedded and distributed in the matrix phase mainly composed of Ce-La-Nd-Pr, resulting in a metallic ribbon composed of endogenous nano Ti-Nb-V alloy powder and Ce-La-Nd-Pr coating. Here, the atomic percentage composition of the endogenous Ti-Nb-V alloy powder was about (Ti-Nb-V) 99.2 (Ce-La-Nd-Pr) 0.5 T 0.3The Ti-Nb-V alloy powder was mainly composed of infinitely miscible Ti-Nb-V single crystal particles with a particle size range of 3 nm to 300 nm. Ce-La-Nd-Pr was dissolved in the intrinsic Ti-Nb-V alloy powder, and the content of T impurity in it was significantly reduced compared to the low-purity Ti, Nb, and V raw materials, while other large amounts of T impurities were enriched in the Ce-La-Nd-Pr coating. In the obtained metal ribbon composed of the intrinsic nano Ti-Nb-V alloy powder and the Ce-La-Nd-Pr coating, the volume percentage content of the intrinsic Ti-Nb-V alloy powder was equivalent to the volume percentage content of the Ti, Nb, and V raw materials during the raw material preparation, which was still about 33 vol%, ensuring the dispersion distribution of the Ti-Nb-V alloy powder in the matrix phase mainly composed of Ce-La-Nd-Pr.
[0182] (4) The Ce-La-Nd-Pr coating in the metal ribbon, which is composed of the endogenous nano Ti-Nb-V alloy powder and the Ce-La-Nd-Pr coating, was removed by dilute hydrochloric acid solution, and the Ti-Nb-V alloy powder, whose main component is (Ti-Nb-V)-(Ce-La-Nd-Pr)-T, was obtained after separation, washing and drying, because the Ti-Nb-V alloy powder does not react with the dilute hydrochloric acid solution. Due to the adsorption of impurities such as oxygen on the surface layer and surface atoms of the exposed Ti-Nb-V alloy powder, the content of T impurities in the obtained Ti-Nb-V alloy powder was slightly higher than that of the endogenous Ti-Nb-V alloy powder.
[0183] [Example 5] The present embodiment provides a metallic ribbon composed of intrinsic submicron Ti-Co alloy powder and Ce-La-Nd-Pr coating, a submicron Ti-Co alloy powder, and a method for producing the same, which includes the following steps:
[0184] (1) The molar ratio of Ti and Co raw materials is 1:1, and the content of the impurity T is about 3 at%. Low-purity Ti and Co raw materials and mixed rare earth raw materials mainly composed of Ce, La, Nd, and Pr are selected. Ti-Ce, Ti-La, Ti-Nd, and Ti-Pr are element combination pairs that do not form intermetallic compounds, and Ti accounts for 50% of the Ti-Co raw material and is the main element. In addition, the melting point of the CoTi intermetallic compound is as high as 1700°C, which is much higher than the melting point of the intermetallic compounds formed by Co and elements such as Ce, La, Nd, and Pr. When Co:Ti is 1:1, Co mainly combines with Ti to form the high-melting point CoTi intermetallic compound, so CoTi alloy powder can be produced based on these element combination pairs.
[0185] (2) Low-purity Ti and Co raw materials were mixed with mixed rare earth raw materials mainly composed of Ce, La, Nd, and Pr in a volume ratio of 1:2, where Ti:Co was in an equimolar ratio. The alloy raw materials were induction melted to obtain an initial alloy melt of (Ti-Co)-(Ce-La-Nd-Pr)-T with a T content of approximately 3 at%.
[0186] (3) The initial alloy melt was rapidly solidified into a ribbon with a thickness of about 300 μm by copper roller strip casting, and during the solidification process, the dispersed particle phase mainly composed of Ti-Co was embedded and distributed in the matrix phase mainly composed of Ce-La-Nd-Pr, resulting in a metallic ribbon composed of endogenous submicron Ti-Co alloy powder and Ce-La-Nd-Pr coating. Here, the atomic percentage composition of the endogenous Ti-Co alloy powder was about (Ti-Co) 99 (Ce-La-Nd-Pr) 0.6 T 0.4The results showed that the Ti-Co alloy powder was mainly composed of intermetallic Ti-Co single crystal particles with a particle size range of 20 nm to 1 μm. The intrinsic Ti-Co alloy powder contained Ce-La-Nd-Pr as a solid solution, and the content of T impurities in the powder was significantly reduced compared to the low purity Ti and Co raw materials, while other large amounts of T impurities were enriched in the Ce-La-Nd-Pr coating. In the obtained metallic ribbon composed of the intrinsic submicron Ti-Co alloy powder and the Ce-La-Nd-Pr coating, the volume percentage content of the intrinsic Ti-Co alloy powder was equivalent to the volume percentage content of the Ti and Co raw materials at the time of raw material preparation, which was still about 33 vol%, ensuring the dispersion distribution of the Ti-Co alloy powder in the matrix phase mainly composed of Ce-La-Nd-Pr.
[0187] (4) The Ce-La-Nd-Pr coating in the metal ribbon, which is composed of the endogenous submicron Ti-Co alloy powder and the Ce-La-Nd-Pr coating, was removed by dilute hydrochloric acid solution, and the Ti-Co alloy powder, which is not easily reacted with the dilute hydrochloric acid solution, was obtained after separation, washing and drying, and the Ti-Co alloy powder, whose main component is (Ti-Co)-(Ce-La-Nd-Pr)-T, was obtained. Due to the adsorption of impurities such as oxygen on the surface layer and surface of the exposed Ti-Co alloy powder, the content of T impurities in the obtained Ti-Co alloy powder was slightly higher than that of the endogenous Ti-Co alloy powder.
[0188] [Example 6] The present embodiment provides a metal sheet composed of intrinsic micron Ti-Co alloy powder and Gd coating, a micron Ti-Co alloy powder, and a manufacturing method thereof, which includes the following steps:
[0189] (1) The molar ratio of Ti and Co raw materials was 1:1, and the content of the impurity T was about 3 at%. Low-purity Ti and Co raw materials and rare earth raw materials mainly composed of Gd were selected. Ti-Gd is an element combination pair that does not form an intermetallic compound, and Ti accounts for 50% of the Ti-Co raw material and is the main element. In addition, the melting point of the CoTi intermetallic compound is high at 1700°C, which is much higher than the melting point of the intermetallic compound formed by elements such as Co and Gd. When Co:Ti is 1:1, Co mainly combines with Ti to form the high-melting point CoTi intermetallic compound, so CoTi alloy powder can be manufactured based on these element combination pairs.
[0190] (2) Low-purity Ti and Co raw materials and rare earth raw materials mainly composed of Gd were mixed in a volume ratio of 30:70, where Ti:Co was in an equimolar ratio, and the alloy raw materials were induction melted to obtain an initial alloy melt of TiCo-Gd-T with a T content of approximately 3 at%.
[0191] (3) The initial alloy melt was rapidly solidified into a thin plate with a thickness of about 2 mm. During the solidification process, the dendritic grain phase mainly composed of Ti-Co was embedded and distributed in the matrix phase mainly composed of Gd, and a thin metal plate was obtained consisting of endogenous micron Ti-Co alloy powder and Ce-La-Nd-Pr coating. The morphology of the solidified structure is shown in Figure 3. Here, the atomic percentage composition of the endogenous Ti-Co alloy powder is about (TiCo) 99.5 Gd 0.3 T 0.2 The Ti-Co alloy powder was mainly composed of intermetallic compound Ti-Co single crystal particles with a particle size range of 1 μm to 60 μm. A small amount of Gd was dissolved in the intrinsic Ti-Co alloy powder, and the content of T impurities in the powder was significantly reduced compared to the Ti and Co raw materials, while other large amounts of T impurities were enriched in the Gd-coated body. In the obtained metal sheet composed of the intrinsic Ti-Co alloy powder and the Gd-coated body, the volume percentage content of the intrinsic Ti-Co alloy powder was equivalent to the volume percentage content of the Ti and Co raw materials at the time of raw material preparation, and was still about 33 vol%, ensuring the dispersion distribution of the Ti-Co alloy powder in the matrix phase mainly composed of Gd.
[0192] (4) The Gd coating in the metal sheet, which is composed of the endogenous micron Ti-Co alloy powder and the Gd coating, was removed by dilute hydrochloric acid solution, and the Ti-Co alloy powder was obtained after separation, washing and drying, because the Ti-Co alloy powder is not easily reacted with the dilute hydrochloric acid solution. The single crystal dendrite morphology is shown in Figure 4. Due to the adsorption of impurities such as oxygen on the surface layer and surface of the exposed Ti-Co alloy powder, the content of T impurities in the obtained Ti-Co alloy powder was slightly higher than that of the endogenous Ti-Co alloy powder.
[0193] [Example 7] This embodiment provides a metal ribbon composed of intrinsic micron Fe alloy powder and La cladding, a micron Fe alloy powder, and a manufacturing method thereof, which includes the following steps:
[0194] (1) We selected a low-purity Fe raw material, both of which contain approximately 2.5 at% of the impurity T, and a rare earth raw material whose main component is La. Since Fe-La is an element combination pair that does not form an intermetallic compound, and both are major elements, it is possible to produce Fe alloy powder based on the combination pair of Fe and La.
[0195] (2) A low-purity Fe raw material and a rare earth raw material mainly composed of La were mixed in a volume ratio of 1:2, and the alloy raw material was induction melted to obtain an Fe-La-T initial alloy melt with a T content of approximately 2.5 at%.
[0196] (3) The initial alloy melt was rapidly solidified into a ribbon with a thickness of about 500 μm by a copper roller strip casting method, and during the solidification process, the dispersed particle phase mainly composed of Fe was embedded and distributed in the matrix phase mainly composed of La, resulting in a metallic ribbon composed of endogenous micron-Fe alloy powder and La cladding. Here, the atomic percentage composition of the endogenous Fe alloy powder was about Fe 99.4 La 0.3 T 0.3The endogenous Fe alloy powder was composed mainly of Fe single crystal particles with a particle size range of 500 nm to 5 μm. La was dissolved in the endogenous Fe alloy powder, and the content of T impurity in it was significantly reduced compared to the low purity Fe raw material, and other large amounts of T impurities were enriched in the La-coated body. In the obtained metal ribbon composed of the endogenous micron Fe alloy powder and the La-coated body, the volume percentage content of the endogenous Fe alloy powder was equivalent to the volume percentage content at the time of raw material preparation, which was still about 33 vol%, ensuring the dispersion distribution of the Fe alloy powder in the matrix phase mainly composed of La.
[0197] (4) The endogenous Fe alloy powder was separated from the matrix La oxide powder by natural oxidation and powdering of the La coating, and the Fe alloy powder was separated from the matrix La oxide powder by using a magnetic field due to the magnetic properties of the Fe alloy powder. Next, the residual La oxide adsorbed on the surface of the Fe alloy powder was completely removed with a small amount of dilute acid solution, and at the same time, the retention of the Fe alloy powder was ensured by controlling the concentration and amount of acid. After washing, separation and drying, the Fe alloy powder was finally obtained.
[0198] [Example 8] This embodiment provides a metal ribbon composed of intrinsic nano Cu alloy powder and Li cladding, a nano Cu alloy powder, and a manufacturing method thereof, which includes the following steps:
[0199] (1) We selected low-purity Cu raw material and low-purity Li raw material, both of which contain approximately 1 at% of the impurity T. Cu-Li is an element combination pair that does not form an intermetallic compound, and both are major elements, so Cu alloy powder can be produced based on the combination pair of Cu and Li.
[0200] (2) Low-purity Cu raw material and low-purity Li raw material were mixed in a volume ratio of 1:3, and the alloy raw material was induction melted to obtain an initial alloy melt of Cu-Li-T with a T content of approximately 1 at%.
[0201] (3) The initial alloy melt was rapidly solidified into a ribbon with a thickness of about 30 μm by a copper roller strip casting method, and during the solidification process, the Cu-based dispersed particle phase was embedded and distributed in the Li-based matrix phase, resulting in a metallic ribbon composed of endogenous nano Cu alloy powder and Li cladding. Here, the atomic percentage composition of the endogenous Cu alloy powder was about Cu. 84.8 Li 15 T 0.2 The particles consisted mainly of single-crystal Cu particles with a large amount of Li dissolved therein, with a particle size ranging from 3 nm to 150 nm. Furthermore, the content of T impurities in the particles was significantly reduced compared to the low-purity Cu raw material, and other large amounts of T impurities were enriched in the Li-coated body.
[0202] (4) The Li coating in the metal ribbon, which is composed of endogenous nano Cu alloy powder and Li coating, was removed using an extremely dilute hydrochloric acid solution. Since the Cu alloy powder does not react easily with the extremely dilute hydrochloric acid solution, after separation, washing, and drying, nano-order Cu alloy powder, whose main component is Cu-Li-T, was obtained.
[0203] [Example 9] This embodiment provides a metal ribbon composed of intrinsic nano Cu alloy powder and Pb cladding, a nano Cu alloy powder, and a manufacturing method thereof, which includes the following steps:
[0204] (1) We selected low-purity Cu and low-purity Pb raw materials, both of which contain approximately 2 at% of the impurity T. Cu-Pb is an element combination pair that does not form an intermetallic compound, and both are major elements, so Cu alloy powder can be produced based on the combination pair of Cu and Pb.
[0205] (2) Low-purity Cu raw material and Pb raw material were mixed in a volume ratio of 1:3, and the alloy raw material was induction melted to obtain an initial alloy melt of Cu-Pb-T with a T content of approximately 1 at%.
[0206] (3) The initial alloy melt was rapidly solidified into a ribbon with a thickness of about 30 μm by a copper roller strip casting method, and during the solidification process, a dispersed particle phase mainly composed of Cu was embedded and distributed in a matrix phase mainly composed of Pb, resulting in a metallic ribbon composed of endogenous nano Cu alloy powder and Pb coatings. Here, the atomic percentage composition of the endogenous Cu alloy powder was about Cu. 99.5 Pb 0.3 T 0.2 The resultant metal ribbon, composed of endogenous nano-Cu alloy powder and Pb-coated body, had a volume percentage content of endogenous Cu alloy powder equivalent to that of the raw material at the time of preparation, which was still about 25 vol%, and ensured the dispersion distribution of Cu alloy powder in the matrix phase mainly composed of Pb. Furthermore, the content of T impurity therein was significantly reduced compared to the low-purity Cu raw material, and other large amounts of T impurities were enriched in the Pb-coated body. In the obtained metal ribbon composed of endogenous nano-Cu alloy powder and Pb-coated body, the volume percentage content of endogenous Cu alloy powder was equivalent to that of the raw material at the time of preparation, which was still about 25 vol%, and ensured the dispersion distribution of Cu alloy powder in the matrix phase mainly composed of Pb.
[0207] (4) The Pb coating in the metal ribbon, which is composed of endogenous nano-Cu alloy powder and Pb coating, was removed using a mixed solution of acetic acid and dilute hydrochloric acid. Since the Cu alloy powder does not react easily with the mixed solution of acetic acid and dilute hydrochloric acid, after separation, washing, and drying, nano-order Cu alloy powder, whose main component is Cu-Pb-T, was obtained.
[0208] [Example 10] The present embodiment provides a metal ribbon composed of intrinsic nano Nb-V-Mo-W alloy powder and Cu cladding, a nano Nb-V-Mo-W alloy powder, and a manufacturing method thereof, which includes the following steps:
[0209] (1) Low-purity Nb, V, Mo, W and Cu raw materials, each with an impurity T content of approximately 1 at%, were selected. Cu-Nb, Cu-V, Cu-Mo and Cu-W are element combination pairs that do not form intermetallic compounds, and Nb, V, Mo and W are main elements that are mutually compatible, so Nb-V-Mo-W alloy powder can be produced based on these combination pairs.
[0210] (2) Low-purity Nb, V, Mo, and W raw materials were mixed with Cu raw material in a volume ratio of 1:2, where the molar ratio of Nb:V:Mo:W was 2:1:1:1. The alloy raw materials were induction melted to obtain an initial alloy melt of (Nb2VMoW)-Cu-T with a T content of approximately 1 at%.
[0211] (3) The initial alloy melt was slowly solidified into a ribbon with a thickness of about 30 μm by copper roller strip casting. During the solidification process, the dispersed particle phase mainly composed of Nb2VMoW was embedded and distributed in the matrix phase mainly composed of Cu, resulting in a metallic ribbon composed of endogenous nano Nb-V-Mo-W alloy powder and Cu cladding. Here, the atomic percentage composition of the endogenous Nb2VMoW alloy powder was about (Nb2VMoW) 99.3 Cu 0.5 T 0.2 The obtained metal ribbon composed of the endogenous nano-Nb-V-Mo-W alloy powder and the Cu cladding had a volume percentage content of the endogenous Nb2VMoW alloy powder equivalent to that of the raw material preparation, which was still about 33 vol%, and ensured the dispersion distribution of the Nb2VMoW alloy powder in the matrix phase mainly composed of Cu. Furthermore, the content of T impurities therein was significantly reduced compared to the low-purity Cu raw material, and other large amounts of T impurities were enriched in the Cu cladding. In the obtained metal ribbon composed of the endogenous nano-Nb-V-Mo-W alloy powder and the Cu cladding, the volume percentage content of the endogenous Nb2VMoW alloy powder was equivalent to that of the raw material preparation, which was still about 33 vol%, and ensured the dispersion distribution of the Nb2VMoW alloy powder in the matrix phase mainly composed of Cu.
[0212] (4) The Cu coating in the metal ribbon, which is composed of endogenous nano-Nb-V-Mo-W alloy powder and Cu coating, was removed using a medium concentration hydrochloric acid solution. Since the Nb2VMoW alloy powder does not react easily with the medium concentration hydrochloric acid solution, after separation, washing and drying, a nano-order alloy powder whose main component is Nb2VMoW was obtained.
[0213] [Example 11] The present embodiment provides a metal sheet composed of intrinsic micron Nb-V-Mo-W alloy powder and Cu cladding, a micron Nb-V-Mo-W alloy powder and a manufacturing method thereof, which includes the following steps:
[0214] (1) Low-purity Nb, V, Mo, W and Cu raw materials, each with an impurity T content of approximately 1 at%, were selected. Cu-Nb, Cu-V, Cu-Mo and Cu-W are element combination pairs that do not form intermetallic compounds, and Nb, V, Mo and W are main elements that are mutually compatible, so Nb-V-Mo-W alloy powder can be produced based on these combination pairs.
[0215] (2) Low-purity Nb, V, Mo, and W raw materials were mixed with Cu raw material in a volume ratio of 1:2, where the molar ratio of Nb:V:Mo:W was 1:1:1:1. The alloy raw materials were induction melted to obtain an initial alloy melt of (NbVMoW)-Cu-T with a T content of approximately 1 at%.
[0216] (3) The initial alloy melt was solidified into a thin plate with a thickness of about 4 mm. During the solidification process, the dendritic dispersed phase mainly composed of NbVMoW was embedded and distributed in the matrix phase mainly composed of Cu, and a metal thin plate was obtained consisting of endogenous micron Nb-V-Mo-W alloy powder and Cu cladding. Here, the atomic percentage composition of the endogenous NbVMoW dendritic alloy powder was about (NbVMoW) 99.6 Cu 0.3 T 0.1 It was mainly composed of high-entropy NbVMoW single crystal particles with a small amount of Cu dissolved therein, with a particle size range of 1 μm to 150 μm. Furthermore, the content of T impurities therein was significantly reduced compared to the low-purity Cu raw material, and other large amounts of T impurities were enriched in the Cu clad. In the obtained metal sheet composed of endogenous micron Nb-V-Mo-W alloy powder and Cu clad, the volume percentage content of the endogenous NbVMoW dendritic alloy powder was equivalent to the volume percentage content at the time of raw material preparation, which was still about 33 vol%, ensuring the dispersed distribution of NbVMoW dendritic alloy powder in the matrix phase mainly composed of Cu.
[0217] (4) The Cu coating in the metal sheet, which is composed of endogenous micron Nb-V-Mo-W alloy powder and Cu coating, was removed by a medium concentration hot hydrochloric acid solution. Since the NbVMoW dendritic alloy powder does not react easily with the medium concentration hot hydrochloric acid solution, after separation, washing and drying, a micron-order dendritic alloy powder whose main component is NbVMoW was obtained.
[0218] The technical features of the above-described embodiments may be combined in any manner. For the sake of brevity, all possible combinations of the technical features in the above embodiments have not been described, but as long as there is no contradiction in the combination of these technical features, they should be considered as within the scope described in this specification.
[0219] The above-described examples merely show some embodiments of the present invention, and the description is relatively specific and detailed, but this should not be understood as limiting the scope of protection of the invention. However, those skilled in the art can make some modifications and improvements without departing from the concept of the present invention, and all of these belong to the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be in accordance with the appended claims.
Claims
1. M a0 A b0 T c0 M with the main element composition a0 A b0 T c0 Step 1 of melting an initial alloy melt, M comprises at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, Co, Ni, Mn, Cu, Ag, Ir, Ru, Re, Os, Tc, W, Cr, Mo, V, Ta, and Nb; When M comprises at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, Co, Ni, Mn, Cu, and Ag, A comprises at least one of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Mg, Ca, Li, Na, K, In, Pb, and Zn; When M includes at least one of Ir, Ru, Re, Os, Tc, W, Cr, Mo, V, Ta, and Nb, A includes Cu; Step 1, in which a0, b0, and c0 represent the atomic percent contents of the corresponding composition elements, and a0+b0+c0=100%, 0<c0≦15%; Said M a0 A b0 T c0 The initial alloy melt is solidified into a solid state, and M precipitated from the melt is a1 A b1 T c1 A covering the dispersed particle phase and the dispersed particles b2 T c2 A step 2 for obtaining a matrix phase, i.e., a metallic material composed of an alloy powder and a coating, wherein 0<c1<c0<c2, and a0 A b0 T c0 In the initial alloy melt, the content of the T element is a1 A b1 T c1 higher than the dispersed particle phase, b2 T c2 The metallic material is manufactured by solidifying an alloy melt, and includes a dispersed particle phase that precipitates during the initial alloy solidification process corresponding to the alloy powder and the cladding, and a matrix phase that covers the dispersed particles. The elemental composition of the alloy powder is mainly M. a1 A b1 T c1 and the elemental composition of the coating is mainly A b2 T c2 wherein M and A each contain one or more metal elements, T is an impurity element including oxygen, a1, b1, c1, b2, and c2 each represent the atomic percent content of the corresponding composition element, and a1+b1+c1=100%, b2+c2=100%, c2>c1>0, and b1>0; the melting point of the alloy powder is higher than that of the coating; the alloy powder contains the A element in solid solution; and M does not form an intermetallic compound between M and A. 1 -A 1 M 1 represents any element of M, A 1 represents any element of A, and the main element of M is selected so that even if the metallic material composed of the alloy powder and the coating is completely melted and then resolidified, an intermetallic compound composed of the main element of M and the main element of A is not formed, and the alloy powder and the coating are produced. 1 -A 1 M that satisfies the element combination conditions 1 The main element of A is M. 1 -A 1 A satisfies the element combination conditions 1 Step 2, which is composed of the element A method for producing a metallic material comprising the alloy powder and the coating, comprising:
2. The method for producing a metallic material composed of an alloy powder and a coating as described in claim 1, characterized in that the shape of the metallic material composed of the alloy powder and the coating is related to the solidification method, and is plate-like when the solidification method is continuous casting, ribbon-like or thin plate-like when the solidification method is molten strip casting, and thread-like when the solidification method is melt drawing.
3. 2. The method for producing a metallic material composed of an alloy powder and a coating according to claim 1, characterized in that T is an element of O including O, H, N, P, S, F, or Cl, and 0<c1≦1.5%.
4. the metallic material composed of the alloy powder and the coating is a ribbon of metallic material composed of the alloy powder and the coating having a thickness of 10 μm to 5 mm; 2. The method for producing a metallic material comprising an alloy powder and a coating according to claim 1, characterized in that the grain size of the alloy powder is in the range of 3 nm to 200 μm.
5. 2. The method for producing a metallic material comprising an alloy powder and a coating according to claim 1, characterized in that 0<b1≦15%.
6. 2. The method for producing a metallic material comprising an alloy powder and a coating according to claim 1, wherein the number of single crystal particles in said alloy powder is 60% or more of the total number of dispersed particles.
7. Said M a0 A b0 T c0 an initial alloy melt is smelted from an alloy feedstock comprising a first feedstock and a second feedstock; The main element composition of the first raw material is M d1 T e1 The main element composition of the second raw material is A d2 T e2 A method for producing a metal material composed of an alloy powder and a coating body as described in claim 1, characterized in that d1, e1, d2, and e2 respectively represent the atomic percent contents of the corresponding composition elements, and 0<e1≦10%, 0<e2≦10%, d1+e1=100%, and d2+e2=100%.
8. A method for producing a metallic material composed of an alloy powder and a coating as described in claim 7, characterized in that the content of T impurity in the alloy powder M a1 A b1 T c1 is significantly reduced compared to that of the first raw material, i.e., c1 is smaller than e1.
9. A metallic material comprising an alloy powder and a coating, A method for producing a metallic material composed of an alloy powder and a coating as described in claim 7, characterized in that the volume percentage content of the M a1 A b1 T c1 alloy powder corresponds to the volume percentage content of the first raw material during raw material preparation.
10. In the metal material composed of the alloy powder and the coating, 2. The method for producing a metallic material composed of an alloy powder and a coating as described in claim 1, characterized in that the lower limit of the volume percentage content of the alloy powder is 1%, and the upper limit is a corresponding volume percentage content that satisfies that the alloy powder can be dispersed in the coating.
11. In the metal material composed of the alloy powder and the coating, 2. The method for producing a metallic material comprising an alloy powder and a coating according to claim 1, characterized in that the volume percentage content range of the alloy powder is 1% to 50%.
12. A metallic material comprising an alloy powder produced by the method according to any one of claims 1 to 11 and a coating body, A method for producing an alloy powder, comprising removing a coating portion while retaining alloy powder that cannot be removed.
13. The method for producing alloy powder according to claim 12, characterized in that the method for removing the coating and retaining the alloy powder includes at least one of acid solution dissolution reaction removal, alkaline solution dissolution reaction removal, vacuum volatilization removal, and natural oxidation-pulverization removal of the coating.
14. 13. The method for producing an alloy powder according to claim 12, wherein M contains Fe, A contains La, the metal material composed of the alloy powder and the coating is a metal strip composed of an Fe alloy powder and a La coating, La is dissolved in the Fe alloy powder, the Fe alloy powder is separated in advance from the matrix La oxide powder by natural oxidation powdering of the La coating, and the Fe alloy powder is separated from the matrix La oxide using a magnetic field due to the magnetic properties of the Fe alloy powder.
15. The method for producing alloy powder according to claim 12, characterized in that the grain size of the alloy powder is in the range of 3 nm to 10 mm.
16. A method for producing a spherical or approximately spherical alloy powder, comprising the steps of: subjecting the alloy powder according to claim 12 to a plasma spheroidizing treatment to obtain a spherical or approximately spherical alloy powder.
17. A method for producing alloy powder according to claim 16, characterized in that the selected particles are subjected to a jet mill pre-grinding and / or screening prior to the plasma spheroidization treatment.
18. A method for producing a metallic material comprising the alloy powder according to any one of claims 1 to 11 and a coating body, comprising: The method for producing a metallic material comprising an alloy powder and a coating, wherein the metallic material is a metallic material for use in paint or composite materials.
19. A method for producing a metallic material composed of alloy powder and a coating, as described in claim 18, characterized in that after preparing a metallic material composed of alloy powder and a coating, the coating is immediately removed, and no other means are used to prevent the alloy powder from being contaminated by impurities including oxygen, but the coating is directly used to protect the alloy powder, which can be directly used as a raw material for downstream production; and when it is necessary to use the alloy powder in downstream production, an appropriate time is selected and the alloy powder is released in an appropriate environment according to the characteristics of the next process, so that the released alloy powder enters the next manufacturing process in the shortest possible time, and the possibility of the alloy powder being contaminated is greatly reduced.
20. A method for producing a metallic material composed of an alloy powder and a coating as described in claim 18, characterized in that a metallic material composed of an alloy powder having an average particle size of less than 1000 nm and a coating is selected, the coating is removed, and the obtained alloy powder is mixed with other components of a paint or composite material simultaneously with or immediately after the removal of the coating so as to reduce the content of impurities including O newly introduced on the powder surface or surface layer after the surface of the alloy powder is exposed, thereby obtaining an alloy powder with high surface activity, and the other components of the paint or composite material are well bonded to the surface of the alloy powder on an atomic scale, thereby obtaining a coating or composite material to which high-purity, high-activity alloy ultrafine powder has been added, which can be applied to the fields of antibacterial coating, weather-resistant coating, stealth coating, radio wave absorbing coating, abrasion-resistant coating, corrosion-resistant coating, and resin-based composite materials.
21. 13. A method for producing an alloy powder according to claim 12, comprising the steps of:
13. The method for producing an alloy powder, wherein the alloy powder is for any one of powder metallurgy, metal injection molding, magnetic materials, and paints.
22. 13. A method for producing an alloy powder according to claim 12, comprising the steps of: The method for producing an alloy powder, wherein the alloy powder is for any one of a catalyst, a sterilization, a metal powder 3D printing, and a composite material.
23. A method for producing a spherical or nearly spherical alloy powder according to claim 16, comprising the steps of: The method for producing a spherical or approximately spherical alloy powder, wherein the spherical or approximately spherical alloy powder is for any one of powder metallurgy, metal injection molding, and metal powder 3D printing.
24. A metallic material comprising an alloy powder and a coating, a metallic material composed of the alloy powder and the coating body includes a dispersed particle phase and a matrix phase coating the dispersed particles, The elemental composition of the alloy powder is mainly M a1 A b1 T c1 and the elemental composition of the coating is mainly A b2 T c2 where M and A each contain one or more metal elements, and T is an impurity element including oxygen; M comprises at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, Co, Ni, Mn, Cu, Ag, Ir, Ru, Re, Os, Tc, W, Cr, Mo, V, Ta, and Nb; When M comprises at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, Co, Ni, Mn, Cu, and Ag, A comprises at least one of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Mg, Ca, Li, Na, K, In, Pb, and Zn; When M includes at least one of Ir, Ru, Re, Os, Tc, W, Cr, Mo, V, Ta, and Nb, A includes Cu; a1, b1, c1, b2, and c2 represent the atomic percent contents of the corresponding composition elements, and a1+b1+c1=100%, b2+c2=100%, c2>c1>0, and b1>0; The melting point of the alloy powder is higher than that of the coating; The alloy powder contains the element A as a solid solution, M which does not form an intermetallic compound between M and A 1 -A 1 Combinations of elements, where M 1 represents any element of M, A 1 represents any element of A, and the main element of M is selected so that even if the metallic material composed of the alloy powder and the coating is completely melted and then resolidified, an intermetallic compound composed of the main element of M and the main element of A is not formed, and the alloy powder and the coating are produced. 1 -A 1 M that satisfies the element combination conditions 1 The main element of A is M. 1 -A 1 A satisfies the element combination conditions 1 A metallic material comprising an alloy powder and a coating, the alloy powder being characterized by being composed of elements.
25. 25. The metallic material comprising the alloy powder and the coating according to claim 24, characterized in that M includes at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, Co, Ni, Mn, Cu, and Ag, A includes at least one of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Mg, Ca, Li, Na, K, In, Pb, and Zn, and T is an impurity element including at least one of O, H, N, P, S, F, and Cl, and 0<c1≦1.5% and 0<b1≦15%.
26. An alloy powder produced by removing a coating of a metallic material composed of the alloy powder according to any one of claims 24 to 25 and a coating, The elemental composition of the alloy powder is mainly M a3 A b3 T c3 a3, b3, c3 represent the atomic percent content of the corresponding element composition, and b3>0, a3+b3+c3=100%, the T element content in the alloy powder is higher than the T element content in the alloy powder according to any one of claims 24 to 25, and c3>c1>0.
27. A spherical or nearly spherical alloy powder obtained by subjecting the alloy powder according to claim 26 to a plasma spheroidizing treatment, The elemental composition of the spherical or nearly spherical alloy powder is mainly M a4 A b4 T c4 a4, b4, and c4 each represent the atomic percent content of the corresponding element composition, and b4>0, a4+b4+c4=100%, the content of the T element in the spherical or approximately spherical alloy powder is higher than that of an alloy powder that has not been subjected to plasma spheroidizing treatment, and c4>c3>c1>0.
28. (1) M a0 A b0 T c0 M with the main element composition a0 A b0 T c0 A process for melting an initial alloy melt, wherein M and A each contain one or more metal elements, T is an impurity element including oxygen, a0, b0, and c0 each represent the atomic percent content of the corresponding composition element, and a0+b0+c0=100%, 0<c0, and M does not form an intermetallic compound between M and A. 1 -A 1 M 1 represents any element of M, A 1 represents any element of A, and the main element of M is M 1 -A 1 M that satisfies the element combination conditions 1 The main element of A is M. 1 -A 1 A satisfies the element combination conditions 1 a process comprising the elements; (2) Said M a0 A b0 T c0 The initial alloy melt is solidified to a solid state, and M is removed from the melt. a1 A b1 T c1 A covering the dispersed particle phase and the dispersed particles b2 T c2 A process for obtaining a metallic material consisting of a matrix phase, i.e. the alloy powder according to any one of claims 24 to 25, and a coating, where 0<c1<c0<c2; A method for producing a metallic material comprising an alloy powder and a coating, comprising:
29. Said M a0 A b0 T c0 An initial alloy melt is melted from an alloy feedstock comprising a first feedstock and a second feedstock, wherein the first feedstock has a major element composition of M d1 T e1 The main element composition of the second raw material is A d2 T e2 A method for producing a metal material composed of an alloy powder and a coating as described in claim 28, characterized in that d1, e1, d2, and e2 represent the atomic percent contents of the corresponding element compositions, and 0<e1≦10%, 0<e2≦10%, d1+e1=100%, and d2+e2=100%.
30. A metallic material comprising the alloy powder according to any one of claims 24 to 25 and a coating body, A method for producing an alloy powder, comprising removing a coating portion while retaining alloy powder that cannot be removed.
31. 27. Use of the alloy powder according to claim 26 in any one of powder metallurgy, metal injection molding, magnetic materials, and paints.
32. 28. Use of the spherical or nearly spherical alloy powder of claim 27 in any one of powder metallurgy, metal injection molding, and metal powder 3D printing.
33. A method for using a metal material comprising the alloy powder according to any one of claims 24 to 25 and a coating in a paint or composite material.
Citation Information
Patent Citations
Method for preparing metal nanoparticles
CN103317141A
Nano porous metal particles and preparation method thereof
CN106811750A
Nano-porous Ag-Cu super-saturated solid solution alloy prepared on basis of various amorphous alloy precursors and method
CN108531762A
Preparation method of metal powder materials
CN111590084A